The Environmental and Economic Effects of European Emissions Trading - Claudia Kemfert; Michael Kohlhaas; Truong Phuoc Truong; Artem Protsenko (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
In 2005, the EU introduced an emissions trading system in order to pursue its Kyoto obligations. This instrument gives emitters the flexibility to undertake reduction measures in the most cost-efficient way and mobilizes market forces for the protection of the earth?s climate. In this paper, we analyse the effects of emissions trading in Europe, with some special reference to the case of Germany. We look at the value of the flexibility gained by trading compared to fixed quotas. The analysis will be undertaken with a modified version of the GTAP-E model using the latest GTAP version 6 data base. It is based on the national allocation plans as submitted to and approved by the EU. We find that, if the NAP is combined with a regional emissions trading scheme, then Germany, Great Britain, and Czech Republic are the main sellers of emissions permits, while Belgium, Denmark, Finland, and Sweden are the main buyers. The welfare gains from regional emissions trading – for the trading sectors only - are largest for Belgium, Denmark, and Great Britain; smaller for Finland, Sweden, and smallest for Germany and other regions. When we take into account the economy-wide and terms of trade effects of emissions trading, however, the (negative) terms of trade effects can offset the (positive) allocative efficiency gains for the cases of the Netherland and Italy, while all other regions ended up with positive net welfare gains. All regions, however, experienced positive increases in real GDP as a result of regional emissions trading.
Keywords: 330; Klimaschutz; Immissionsschutz; Emissionsrechte; Emissionshandel; Wirtschaftliche Effizienz; Internationale Umweltpolitik; EU-Umweltpolitik; Deutschland; EU-Staaten; Welt